2020
DOI: 10.1523/jneurosci.1749-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Mediates Cuprizone-Induced Loss of Oligodendrocytes and Demyelination

Abstract: Multiple sclerosis (MS) is a chronic demyelinating disease of the CNS. Cuprizone (CZ), a copper chelator, is widely used to study demyelination and remyelination in the CNS, in the context of MS. However, the mechanisms underlying oligodendrocyte (OL) cell loss and demyelination are not known. As copper-containing enzymes play important roles in iron homeostasis and controlling oxidative stress, we examined whether chelating copper leads to disruption of molecules involved in iron homeostasis that can trigger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 70 publications
(106 reference statements)
4
116
1
Order By: Relevance
“…Several studies have shown that CPZ-treated mice show extensive demyelination, metabolic stress and oligodendrocyte apoptosis [7,8]. In fact, mice fed with 0.2% CPZ between 4 to 6 weeks revealed demyelination and had abnormal behavior like fewer social interaction [9,10]. The pathological effects of CPZ are based on many reasons such as : (a) disruption of Cu homeostasis [5], (b) inhibition of enzymes [11], (c) megamitochondria due to ssion inhibition and generation of free radicals, (d) increased oxidative stress due to declined function of the antioxidant enzymes catalase and superoxide dismutase (SOD), reduction of glutathione (GSH) levels, elevation of Fe + 2 in mitochondrial matrix and cytosol and lipid peroxidation [5,12], (e) increases of the activity of plasmalogenase and phospholipase A2 (PLA2) and arachidonic acid (AA) which can produce prostaglandins and leukotrienes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CPZ-treated mice show extensive demyelination, metabolic stress and oligodendrocyte apoptosis [7,8]. In fact, mice fed with 0.2% CPZ between 4 to 6 weeks revealed demyelination and had abnormal behavior like fewer social interaction [9,10]. The pathological effects of CPZ are based on many reasons such as : (a) disruption of Cu homeostasis [5], (b) inhibition of enzymes [11], (c) megamitochondria due to ssion inhibition and generation of free radicals, (d) increased oxidative stress due to declined function of the antioxidant enzymes catalase and superoxide dismutase (SOD), reduction of glutathione (GSH) levels, elevation of Fe + 2 in mitochondrial matrix and cytosol and lipid peroxidation [5,12], (e) increases of the activity of plasmalogenase and phospholipase A2 (PLA2) and arachidonic acid (AA) which can produce prostaglandins and leukotrienes [13].…”
Section: Introductionmentioning
confidence: 99%
“…While CUP has been used for over 50 years as a model of demyelination (Carlton, 1966, 1967; Suzuki & Kikkawa, 1969), there has not been a general consensus of how CUP disrupts oligodendrocytes (Ács & Komoly, 2012; Arnett et al, 2002; Goldberg et al, 2013). Changes in oligodendrocyte mitochondrial/energy and lipid metabolism result in selective oligodendrocyte loss (Praet et al, 2014) with recent data implicating ferroptosis (Jhelum et al, 2020). Thus, CUP is considered a direct oligodendrocyte toxin that in turn results in a secondary microgliosis.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with previous findings in other neurodegenerative diseases such as Parkinson’s disease 24 . The interplay of these two nodes in regulating CNS homeostasis needs to be further explored in subsequent studies, and in particular in progressive MS. Interestingly, iron mediated signaling can lead to an inflammatory form of cell death, called ferroptosis and its role in MS should be further explored 25 . This form of cell death is regulated by GPX4, which is a enzyme responsible for blocking the deleterious iron-induced cellular response and is altered in our MS transcriptomic data sets 26,27 .…”
Section: Discussionmentioning
confidence: 99%